Exploration and Practice of Sustainable Development Path - He, Linxin (International Journal of Global Economics and Management, 2025)
Sustainable development, key to contemporary issues, aims at eco-economic-social harmony. This study analyzes its theoretical basis, challenges, and proposes strategies. It outlines sustainable development concepts, summarizes research, and highlights urgent challenges like environmental degradation and climate change. Three models—green economy, circular economy, and renewable energy—are introduced and evaluated. China's urban-rural integration model and Norway/Germany's green transformation examples further verify the schemes' practicality and feasibility. Based on the comprehensive consideration of the above path selection, this paper finally puts forward a series of policy initiatives to advocate the close collaboration of government, business and the public to accelerate the achievement of the Sustainable Development Goals. This study is expected to provide useful reference for the choice of sustainable development path in the future, and stimulate the attention and active participation of the wider community on this issue.